Identidade docente na creche: o encontro entre sujeitos em diferentes tempos formativos no Programa de Residência Pedagógica (PRP) - Rodrigues, Jéssica Pires (Universidade Federal de São Carlos, 2021)
This research working is part of the Graduate Program in Education, at the Federal University of São Carlos in Brazil, in the line of research on Teacher Education, and seeks to analyze the process of constitution of the teaching identity in nursery school as of the encounter between two types of different formative evaluation: the intern, through in initial training process and the teacher, an active professional, in a continuing education development process. Therefore, within a qualitative research perspective, it will be use bibliographical research and narrative interview. It will be utilized Nóvoa (1989 and 1991) and Pimenta (1999) to deal with the teaching profession; Dubar (2006), Pimenta and Lima (2017) and Nóvoa (1991) for teacher identity; Pimenta and Lima (2017) and Rodrigues (2013) to talk about internship and Campos (2008), Cerisara (1999) and Kuhlmann Junior (1998 and 2000) to talk about the nursery school and its specificities. Narrative interviewing were conducted with teachers and interns, students from the Pedagogy course at the Federal University of São Carlos (UFSCar) – Campus Sorocaba, and teachers from a public nursery school in the city of Sorocaba, countryside of São Paulo, participants of the Pedagogical Residency Program (PRP) in the year 2018. As it may realise that the meetings that took place in nursery school during the Pedagogical Residency Program (PRP) constituted an important opportunity to consolidate the options and intentions of teaching in nursery school for the interns who will be fundamental to teaching identity these, allowing teachers a continuing education development process, valuing their knowledge and contributing for the reaffirmation of their teaching identity. Collaboration between university and nursery school in initial and continuing teacher education proved to be as possible as it is necessary as a teacher education policy.
Teacher identity in nursery school: the encounter between subjects at different formative times in the Pedagogical Residency Program (PRP)
Keywords: Identidade docente; Creche; Estágio supervisionado; Formação docente; Teaching identity; Nursery; Supervised internship; Teacher education; CIENCIAS HUMANAS::EDUCACAO